Evaluasi Kinerja UMKM Ditinjau Dari Aspek Keuangan Dan Aspek Pemasaran Pasca Pandemi Covid 19 - Ardiyani, Komala; Ilmiani, Amalia; Maulidin Fachrur, Muhammad (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to provide empirical evidence regarding the importance of evaluating the performance of MSMEs after the Covid-19 pandemic. Using financial aspects and marketing aspects, the study tries to examine the extent to which financial and marketing aspects affect the performance of MSMEs. A total of 75 Batik SMEs domiciled in Pekalongan City participated in this study. The analysis technique used is multiple linear regression with hypothesis testing. The results of the study revealed that the financial aspect and the marketing aspect contributed to the improvement of the performance of Batik UMKM after the Covid 19 pandemic, so that the proposed hypothesis was supported. The financial aspect has a significant positive effect on the performance of MSMEs, as well as the marketing aspect has a significant positive effect on the performance of MSMEs. Developing countries such as Indonesia see MSMEs as a way out of poverty so it is necessary to create superior MSMEs so that they can compete in the global market. Great attention through financial and marketing aspects can realize competitive small and medium scale industries.